Stable Occupancy of the Crimean-Congo Hemorrhagic Fever Virus-Encoded Deubiquitinase Blocks Viral Infection - Florine E. M. Scholte (American Society for Microbiology, 2019)
ABSTRACT Crimean-Congo hemorrhagic fever virus (CCHFV) infection can result in a severe hemorrhagic syndrome for which there are no antiviral interventions available to date. Certain RNA viruses, such as CCHFV, encode cysteine proteases of the ovarian tumor (OTU) family that antagonize interferon (IFN) production by deconjugating ubiquitin (Ub). The OTU of CCHFV, a negative-strand RNA virus, is dispensable for replication of the viral genome, despite being part of the large viral RNA polymerase. Here, we show that mutations that prevent binding of the OTU to cellular ubiquitin are required for the generation of recombinant CCHFV containing a mutated catalytic cysteine. Similarly, the high-affinity binding of a synthetic ubiquitin variant (UbV-CC4) to CCHFV OTU strongly inhibits viral growth. UbV-CC4 inhibits CCHFV infection even in the absence of intact IFN signaling, suggesting that its antiviral activity is not due to blocking the OTU’s immunosuppressive function. Instead, the prolonged occupancy of the OTU with UbV-CC4 directly targets viral replication by interfering with CCHFV RNA synthesis. Together, our data provide mechanistic details supporting the development of antivirals targeting viral OTUs. IMPORTANCE Crimean-Congo hemorrhagic fever virus is an important human pathogen with a wide global distribution for which no therapeutic interventions are available. CCHFV encodes a cysteine protease belonging to the ovarian tumor (OTU) family which is involved in host immune suppression. Here we demonstrate that artificially prolonged binding of the OTU to a substrate inhibits virus infection. This provides novel insights into CCHFV OTU function during the viral replicative cycle and highlights the OTU as a potential antiviral target.